Harmony of Culture and Education: A Content Analysis of the Role of Banjar Songs in Shaping Pancasila Student Profile - Widiantho, Susyam; Wadiyo, Wadiyo; Rihidi, Tjetjep Rohendi; Suharto (Institut Seni Indonesia Denpasar, 2025)
The Pancasila Student Profile embodies Indonesian students as lifelong learners who have global competence and behave according to the values of Pancasila. The Pancasila Student Profile can be achieved through folk songs. Banjar folk song, as one of the art forms produced from the culture originating from the South Kalimantan region, has an appropriate meaning and can be used to realise the Pancasila Student Profile. The purpose of this research is to analyse the needs of Banjar songs to obtain data and information about: (1) Banjar songs that are relevant to the Pancasila Student Profile; (2) The needs of students in shaping the character of the Pancasila Student Profile through banjar songs; (3) Character values presented in banjar songs. This research was conducted in stages: planning, data collection, reduction, and conclusion drawing. Data analysis used a qualitative descriptive method. The results showed that: (1) Banjar songs have values and meanings that are relevant to the character building of Pancasilais students; (2) Students need Banjar songs in growing the character of Pancasilais students; This finding has confirmed that Banjar songs are a product of mass culture, namely works of art produced from the cultural ecosystem. Thus, Banjar songs can be an alternative in shaping the character of Pancasila students; (3) Banjar songs have character values of noble character, global diversity, cooperation, independence, critical and creative reasoning that are relevant to the elements of the Pancasila Student Profile.